1991
DOI: 10.3354/meps072111
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activity of certain enzymes in sea urchin embryos and larvae after exposure of adult organisms to heavy metals

Abstract: The activity of acid and alkaline phosphatases, glucose-6-phosphatase. ~g~+ -~T P a s e and glucose-6-phosphate dehydrogenase was investigated in embryos and larvae obtained from gametes of the sea urchin Strongylocentrotus nudus exposed for 30 d to increased zinc, copper and cadmium concentrations (100, 25 and 50 ltg 1-l. respectively). Exposure of parent sea urchins to zinc resulted in increased M g 2 + -~T P a s e activity and decreased glucose-6-phosphate degydrogenase activity in larvae at the stage of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Mixtures of copper and zinc or copper and cadmium produced more than additive effects in suppressing embryonic development of sea urchins than could be predicted on the basis of individual metals; however, copper-nickel mixtures acted additively (Kobayashi and Fujinaga, 1976). In another study with sea urchins, adults of the comparatively sensitive Strongylocentrotus nudus were held in seawater containing 0.025 mg Cu/L for 30 days and the resultant embryos reared in uncontaminated seawater for 30 days (Durkina and Evtushenko, 1991). Food consumption of adults decreased after day 16; there was accelerated development of pluteal stages; and all developmental stages had increased activities of acid phosphatase (Durkina and Evtushenko, 1991).…”
Section: Coppermentioning
confidence: 99%
See 1 more Smart Citation
“…Mixtures of copper and zinc or copper and cadmium produced more than additive effects in suppressing embryonic development of sea urchins than could be predicted on the basis of individual metals; however, copper-nickel mixtures acted additively (Kobayashi and Fujinaga, 1976). In another study with sea urchins, adults of the comparatively sensitive Strongylocentrotus nudus were held in seawater containing 0.025 mg Cu/L for 30 days and the resultant embryos reared in uncontaminated seawater for 30 days (Durkina and Evtushenko, 1991). Food consumption of adults decreased after day 16; there was accelerated development of pluteal stages; and all developmental stages had increased activities of acid phosphatase (Durkina and Evtushenko, 1991).…”
Section: Coppermentioning
confidence: 99%
“…In another study with sea urchins, adults of the comparatively sensitive Strongylocentrotus nudus were held in seawater containing 0.025 mg Cu/L for 30 days and the resultant embryos reared in uncontaminated seawater for 30 days (Durkina and Evtushenko, 1991). Food consumption of adults decreased after day 16; there was accelerated development of pluteal stages; and all developmental stages had increased activities of acid phosphatase (Durkina and Evtushenko, 1991).…”
Section: Coppermentioning
confidence: 99%
“…Mechanisms of copper toxicity for such organisms are likely to be very different from those of fish (Grosell et al 2007). In marine invertebrates copper toxicity has been associated with respiratory impairment, in particular by disrupting haemocyanin functions (Bielmyer et al 2005, Lee et al 2010, Jakimska et al 2011 as well as disruption of protein and enzyme activity (Flemming & Trevors 1989, Durkina & Evtushenko 1991. In addition, copper has been shown to causes DNA damage both in vitro and in vivo (Haldsrud & Krokje 2009, Al-Shami et al 2011.…”
Section: Coppermentioning
confidence: 99%
“…fertilised eggs may fail to develop into normal embryos and larvae. In echinoderms, only one study has examined the long-term effects of copper exposure in adults on larval performance, in the sea urchin Strongylocentrotus nudus (Durkina & Evtushenko 1991). While the authors reported no adverse effects, though a slight increase in developmental rate, further work would be needed to confirm this pattern in other species.…”
Section: Field Populationsmentioning
confidence: 99%
“…A decrease in gamete quality or fertilisation success following adult exposure to metals has been documented in sea urchins for cadmium (Au et al 2001) andlead (Nacci et al 2000), but has not been examined for copper. Durkina & Evtushenko (1991) reported that adult exposure to copper increased the developmental rate of larvae, but they did not evaluate the effects on fertilisation success.…”
Section: Introductionmentioning
confidence: 99%